Revisiting fruit and vegetable determinants: Evidence from Latin America - Silva, Andres; Astorga, Andrés; Durán-Agüero, Samuel; Domper, Alejandra (Frontiers in Sustainable Food Systems, 2023)
Introduction In the past decade, the public health discussion regarding fruit and vegetable (FV) consumption has been dominated by economic and physical accessibility. Methods Using an online survey in four Latin American countries, we applied a set of tobit models to compare the determinants of desirable and current consumption of FV levels for satisfied and unsatisfied respondents. Results We found that, even when consuming less than five FV portions a day, most of the respondents were satisfied with their current FV consumption level. Satisfied respondents consumed significantly more FV than unsatisfied ones. In general, the desirable and current consumption of FV levels were associated with different sets of determinants, while years of education were relevant in both cases. Finally, in a hypothetical case where unsatisfied respondents would not face any physical or economic access restrictions, unsatisfied respondents would not reach the goal of five FV portions a day. Discussion Assuming that physical and economic access improved, this would automatically increase FV to reach the five-a-day recommendation may be inaccurate in some cases. We also need to take mental access into account. We may ask how to improve the desirable level of FVs and then how to close the gap between the current and desirable FV levels.